Vagueness, contextualism, and ellipsis - Elbourne, P (Linguistic Society of America, 2019)
Stanley (2003) has argued that contextualist theories of vagueness are inconsistent with a certain fact about the interpretation of indexicals in Verb Phrase ellipsis, namely that the semantic content of an indexical in an elided verb phrase must be the same as the semantic content of the corresponding indexical in the antecedent verb phrase. In this paper, some counterexamples are adduced to undermine confidence in this generalization and hence Stanley’s argument as a whole.